Early Hyperglycemia is Associated with Sepsis in Pediatric Burn Patients: A 4-year Study in the Largest Burn Unit in Eastern Indonesia - Burhan Husein; Iswinarno Doso Saputro; Magda Rosalina Hutagalung; Vijayendran Swaminathan; Hanif Ardiansyah Sulistya (Biomolecular and Health Science Journal)
Introduction: Pediatric burn injuries are associated with high morbidity and mortality, with sepsis being a major complication due to immature immune responses. Early physiological disturbances such as hypoalbuminemia and hyperglycemia are common in extensive burns and may contribute to increased infection risk. This study aimed to assess the association between early hypoalbuminemia and hyperglycemia with the development of sepsis in pediatric burn patients. Methods: We conducted a retrospective cross-sectional study using a total sampling of pediatric burn patients admitted to the Burn Unit of Dr. Soetomo General Hospital, Surabaya, from January 2020 to December 2023. A total of 63 patients met the inclusion criteria. Demographic, clinical, and laboratory data were collected and analyzed using the Chi-square test. Results: Of the 63 patients, 58.7% were male, with the majority aged 0–5 years. Scald injuries were the leading cause (61.9%). The median hospital stay was 15 days, longer in those with burn surface area >30%. Early hypoalbuminemia was not significantly associated with sepsis (P = 0.163; χ² = 1.946). However, early hyperglycemia showed a significant association with sepsis (P = 0.01; χ² = 6.564), indicating an increased risk of sepsis in patients presenting with elevated blood glucose levels. Conclusions: Early hyperglycemia may worsen immune response and increase the risk of sepsis in pediatric burn patients, while hypoalbuminemia likely reflects acute inflammation without direct impact on sepsis. These findings highlight the importance of early glucose monitoring and control in improving outcomes. Further studies with larger samples are recommended.